THE LINGUISTIC DEVELOPMENT OF THE FOURTH AND SIXTH GRADERS: THE TYPES AND SUBTYPES OF THEIR SYNTACTIC CONSTRUCTIONS - Kurniawansah, Alfi (Linguists : Journal of Linguistics and Language Teaching, 2018)
This research aims at investigating how the elementary-school students write in English since they are already taught how to write the spellings of the English words and how to speak the language. The objectives of this research were to identify what syntactic types and subtypes are likely formed by the fourth and sixth graders of elementary school when they produce a situational description disregarding the errors that the learners have made. Such errors are considered to be developmental since they are inevitable in the process of learning and they are, therefore, not the concern of this paper. This study was done to the fourth-grade students and sixth-grade students of elementary school. All the samples were given a situational picture of a living room where a father, mother, son and daughter got together, and were asked to describe the picture according to their own perception. They were given only 45 minutes to do the assessment as it was the allocated time available. All the sentential constructions produced by the students were counted and analyzed in order to find the types and subtypes of sentences the fourth graders and the sixth graders used in their situational descriptive writing. The results of the study show that it the constructions of the sixth graders’ compound sentences are mostly simple in the sense that they conjoin only two simple sentences. Similarly, the constructions of their complex sentences are not very complex too. They consist of only one independent clause and one dependent clause. In their syntactic constructions compound and complex sentences are not found.